2000
DOI: 10.1073/pnas.140209197
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of terpenoids: 4-Diphosphocytidyl-2- C -methyl- d -erythritol kinase from tomato

Abstract: The putative catalytic domain (residues 81-401) of a predicted tomato protein with similarity to 4-diphosphocytidyl-2-C-methyl-D-erythritol kinase of Escherichia coli was expressed in a recombinant E. coli strain. The protein was purified to homogeneity and was shown to catalyze the phosphorylation of the position 2 hydroxy group of 4-diphosphocytidyl-2-C-methyl-D-erythritol at a rate of 33 mol⅐mg ؊1 ⅐min ؊1 . The structure of the reaction product, 4-diphosphocytidyl-2-C-methyl-D-erythritol 2-phosphate, was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(45 citation statements)
references
References 27 publications
4
41
0
Order By: Relevance
“…An isopentenyl phosphate kinase in E. coli has been reported previously (21); however, this enzyme was later found to be a 4-diphosphocytidyl-2-C-methyl-Derythritol kinase involved in the DXP pathway (24). Further analysis of a more purified enzyme preparation showed that the E. coli enzyme did not possess isopentenyl monophosphate kinase activity (30). There is no significant sequence similarity between M. jannaschii IP kinase and E. coli 4-diphosphocytidyl-2-C-methyl-D-erythritol kinase.…”
Section: Resultsmentioning
confidence: 96%
“…An isopentenyl phosphate kinase in E. coli has been reported previously (21); however, this enzyme was later found to be a 4-diphosphocytidyl-2-C-methyl-Derythritol kinase involved in the DXP pathway (24). Further analysis of a more purified enzyme preparation showed that the E. coli enzyme did not possess isopentenyl monophosphate kinase activity (30). There is no significant sequence similarity between M. jannaschii IP kinase and E. coli 4-diphosphocytidyl-2-C-methyl-D-erythritol kinase.…”
Section: Resultsmentioning
confidence: 96%
“…A plant gene homologous to ychB had previously been retrieved in a bioinformatic approach designed to identify ESTs encoding metabolite kinases in a cDNA library from peppermint oil gland secretory cells (Lange and Croteau, 1999a). Although these authors proposed that the encoded protein could phosphorylate isopentenyl monophosphate to IPP in the putative last step of the MEP pathway, further experiments with the recombinant enzymes from E. coli and tomato (Lycopersicon esculentum) showed that they catalyzed the phosphorylation of CDP-ME to CDP-MEP at a much higher rate, indicating that this is the true metabolic role of the enzyme (Rohdich et al, 2000a). Although the results described above strongly suggested that ygbP (ispD), ychB (ispE),and ygbB (ispF) encoded enzymes directly involved in the MEP pathway, a clear-cut demonstration was provided by the development of a neat experimental system originally designed for the cloning of unknown MEP pathway genes in E. coli (Kuzuyama et al, 2000a(Kuzuyama et al, , 2000bTakagi et al, 2000;Campos et al, 2001a).…”
Section: To 1998 From the Precursors To The Identification Of The Fimentioning
confidence: 99%
“…This is evidenced by the specific labeling pattern of typical chloroplast isoprenoids from the photosynthetic apparatus (phytol 5 from chlorophylls, plastoquinone 6, carotenoids 7) [20] or sec-ondary metabolites, whose biosynthesis is related to plastid-like structures (isoprene 1, monoterpenes, diterpenes) [23][24][25][26][27][28]. Definitive proof for the localization of the MEP pathway in chloroplasts is given by the presence of a nucleotide sequence corresponding to a plastid-targeting peptide in the genes encoding the plant enzymes of the MEP pathway [35,[73][74][75][76][77]. In unicellular green algae, however, no dichotomy in the isoprenoid biosynthesis was observed [78].…”
Section: Conclusion: Distribution Of the Pathways For Isoprenoid Biosmentioning
confidence: 99%